Parallel multiprocessing and scheduling on the heterogeneous Xeon+FPGA platform. - Rodríguez-Moreno, Andrés; González-Navarro, María Ángeles; Asenjo-Plaza, Rafael; Corbera-Peña, Francisco Javier; Gran-Tejero, Rubén; Suárez Gracia, Darío; Núñez-Yáñez, José (Springer, 2020)
Herogeneous computing that exploits simultaneous co-processing with different device types has been shown to be effective at both increasing performance and reducing energy consumption. In this paper, we extend a scheduling framework encapsulated in a high-level C++ template and previously developed for heterogeneous chips comprising CPU and GPU cores, to new high-performance platforms for the data center, which include a cache coherent FPGA fabric and many-core CPU resources. Our goal is to evaluate the suitability of our framework with these new FPGA-based platforms, identifying performance benefits and limitations.We target the state-of-the-art HARP processor that includes 14 high-end Xeon classes tightly coupled to a FPGA device located in the same package. We select eight benchmarks from the high-performance computing domain that have been ported and optimized for this heterogeneous platform. The results show that a dynamic and adaptive scheduler that exploits simultaneous processing among the devices can improve performance up to a factor of 8 × compared to the best alternative solutions that only use the CPU cores or the FPGA fabric. Moreover, our proposal achieves up to 15% and 37% of improvement compared to the best heterogeneous solutions found with a dynamic and static schedulers, respectively.
Keywords: Computación heterogénea; Arquitectura de ordenadores; Heterogeneous architecture; Heterogeneous scheduling; FPGA; Parallel_for template; Hybrid algorithm; Adaptive chunk size